Fatigue Characteristics in Patients with Type 2 Diabetes Mellitus and Diabetic Ulcer Complications - Liya Maya Listianah; Mohammad Arifin Noor; Suyanto Suyanto (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Fatigue is a common complaint in individuals with type 2 DM accompanied by diabetic ulcers due to metabolic disorders, chronic pain, and limited activity. This condition can last for a long time and have an impact on the patient's physical and psychological function. This study aims to describe the characteristics of Fatigue in patients with type 2 diabetes mellitus who experience complications of diabetic ulcers. Methodology: This study used an analytical descriptive design with a cross-sectional approach, involving 133 respondents as a sample obtained through purposive sampling techniques. The research instrument used Multidimensional Fatigue Inventory-20 (MFI-20). Data analysis was carried out descriptively using frequency distribution and descriptive statistics. Results: The mean age of the respondents was 57.64 years (95% CI 56.63–58.65). Most of the respondents were female (55.6%), had diabetes for more than 5.56 years, had a junior high school education level (31.6 %), and the majority of the job types did not work (27.8%). As many as 72.9% of respondents experienced Fatigue . Discussion: The characteristics of type 2 diabetes mellitus patients with diabetic ulcers who experience Fatigue show variations based on age, sex, education level, type of occupation, and length of illness. The condition of diabetic ulcers contributes to increased Fatigue through limited mobility, pain, and psychological stress.